2018
DOI: 10.1088/1741-2552/aa9bfb
|View full text |Cite
|
Sign up to set email alerts
|

Remapping cortical modulation for electrocorticographic brain–computer interfaces: a somatotopy-based approach in individuals with upper-limb paralysis

Abstract: These results demonstrate the feasibility of ECoG-based BCI systems for individuals with paralysis as well as highlight some of the key challenges that must be overcome before such systems are translated to the clinical realm. ClinicalTrials.gov Identifier: NCT01393444.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 88 publications
1
44
0
Order By: Relevance
“…For example, a recent study using ECoG in humans has shown that S1 activates before M1 during hand movement (Sun et al , 2015). In addition, high accuracy decoding of hand and finger movements from S1 has been demonstrated by recent BCI studies performed with paralyzed patients (Wang et al , 2013; Degenhart et al , 2018) and people with arm amputation (Kikkert et al , 2016; Bruurmijn et al , 2017). These results support data from earlier fMRI and electrocortical stimulation studies, in particular the findings 1) in individuals with spinal cord injury, who show fMRI activation of S1 during attempted movements (Cramer et al , 2005; Hotz-boendermaker et al , 2008, 2011); 2) in individuals with induced ischemic nerve blocking, who had preserved fMRI responses without sensory feedback (Christensen et al , 2007); and 3) in individuals with epilepsy who show isolated and complex hand responses upon cortical stimulation of S1 (Nii et al , 1996; Haseeb et al , 2007).…”
Section: Discussionmentioning
confidence: 89%
“…For example, a recent study using ECoG in humans has shown that S1 activates before M1 during hand movement (Sun et al , 2015). In addition, high accuracy decoding of hand and finger movements from S1 has been demonstrated by recent BCI studies performed with paralyzed patients (Wang et al , 2013; Degenhart et al , 2018) and people with arm amputation (Kikkert et al , 2016; Bruurmijn et al , 2017). These results support data from earlier fMRI and electrocortical stimulation studies, in particular the findings 1) in individuals with spinal cord injury, who show fMRI activation of S1 during attempted movements (Cramer et al , 2005; Hotz-boendermaker et al , 2008, 2011); 2) in individuals with induced ischemic nerve blocking, who had preserved fMRI responses without sensory feedback (Christensen et al , 2007); and 3) in individuals with epilepsy who show isolated and complex hand responses upon cortical stimulation of S1 (Nii et al , 1996; Haseeb et al , 2007).…”
Section: Discussionmentioning
confidence: 89%
“…In other words, BCI systems can provide alternative communication channels for LIS patients [ 3 ]. BCIs can be realized using various neuroimaging modalities, such as electrocorticography (ECoG) [ 4 , 5 ], electroencephalography (EEG) [ 6 , 7 ], magnetoencephalography (MEG) [ 8 , 9 ], functional near-infrared spectroscopy (fNIRS) [ 10 , 11 ], and functional magnetic resonance imaging (fMRI) [ 12 , 13 ]. An invasive signal recording technique, such as ECoG, requires a surgical operation to place recording electrodes on the cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Biomimetic decoding exploits the mapping which relates neuronal activity to limb movement before the patient began to suffer from motor disabilities; that is, it uses the activity of neurons naturally devoted to the control of a specific limb to compute the commands sent to the corresponding prothesis or orthosis. These decoders are often referred to as “direct” decoders [“direct motor Brain Machine Interfaces” (Waldert et al, 2009 ), “direct mapping” (Degenhart et al, 2018 )]. Most biomimetic decoders are kinematic.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the brain patterns that are used to control the prosthesis or orthosis movements are elicited by mental tasks, such as motor imageries (somatotopic remapping), and cognitive tasks. “Mental-task” decoding (Waldert et al, 2009 ) or “abstract” mapping (Degenhart et al, 2018 ) are some of the terms that have been used in the literature to refer to BCIs based on unnatural motor imageries and cognitive tasks or strategies. Various mental tasks have been used to elicit intention-specific and distinguishable brain patterns for neural control in motor BCI systems (Waldert et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation